Factors affecting the sharing of information on quality durian production by farmers in Rayong Province, Thailand - N. Meehat; Suneeporn Suwanmaneepong; Chanhathai Kerdsriserm (International Journal of Agricultural Technology, 2025)
This study examined the factors influencing information exchange among durian farmers in Rayong Province, Thailand, regarding high-quality production practices. A survey of 54 farmers, equally distributed by gender, revealed an average age of 44.52 years, with most being married and holding at least a bachelor’s degree. The majority cultivated Monthong durian on plots of five rai or larger and had over five years of experience. Farmers applied their knowledge of water and maintenance systems, among other practices. The study findings revealed that motivation levels correlated with the farmers’ propensity to share information. Factors influencing information exchange, ranked from the highest to the lowest average value, were knowledge promotion and development (x̄ = 4.24), marketing (x̄ = 4.00), along with social relations and acceptance (x̄ = 3.46), resulting in a high overall level (x̄ = 3.90). Multiple regression analysis revealed traditional water management wisdom as the sole significant predictor of information-sharing behavior among the 11 variables tested, influencing both knowledge promotion (β = 0.573, p = 0.002) and marketing information sharing (β = 0.467, p = 0.011). Demographic characteristics, farming practices, and other production knowledge had no significant impact on farmers' sharing motivations.
Keywords: Indigenous Knowledge Systems and Agriculture; Urban Planning and Valuation; Agricultural Innovations and Practices